Mystical Narrative as a Mechanism of Social Control over Customary Norms in Sugar Factory Films - Nur Amelia; Joko Hariadi (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
The film Pabrik Gula presents a mystical narrative that represents social control in Javanese society through the symbolism of sacred spaces, customary prohibitions and myths. The factory is not just a workplace, but a sacred space guarded by unwritten norms, such as the prohibition of going out at night, which is considered a time of domination by spirits. Violations of this norm, experienced by Endah, Naning and Hendra, trigger mystical terror as a spiritual sanction. The terror serves as a visual medium that confirms that myth is not just a story, but a means of internalising social values. This research uses a qualitative approach with text analysis and hermeneutic methods, within the framework of literary anthropology and Malinowski's functionalism. The analysis was conducted by interpreting the symbolism, prohibitions, and mystical consequences in the context of East Javanese culture. The results of the study show that the myth in the film functions as a social control tool that remains relevant in modern society.